Design and Analysis of the AlNiCo Hybrid Magnet in EMS Maglev Vehicles - Lv Chao; Li Jie (MATEC Web of Conferences, 2017)
In order to solve the problem of hybrid electromagnet lock orbit, we design a new type of AlNiCo-NdFeB hybrid levitation electromagnet. The theoretical analysis has be carried on and mathematical model is established for AlNiCo-NdFeB hybrid levitation electromagnet. Through two dimensional simulation, the electromagnetic characteristics of the suspended electromagnet are analyzed in the 3 typical operating conditions , which are in heavy load at gap 8mm, in full load at gap 16mm and in no-load at gap 3mm. And it’s compared with the traditional electromagnetic magnet and NdFeB hybrid electromagnet. Calculation and analysis show that the new hybrid levitation electromagnet can effectively solve the problems of the electromagnet lock orbit, at the same time, have a good dynamic performance and suspension regulation performance.